INTERNAL AUDIT AS AN EFFORT TO INCREASE TRANSPARENCY AND ACCOUNTABILITY OF FINANCIAL STATEMENTS AT SD MUHAMMADIYAH 3 IKROM WAGE SIDOARJO - Biduri, Sarwenda; Maryanti, Eny; Soeprijanto, Noerwachid; Firnata, Tifani Angga (Journal of Social Comunity Services, 2025)
Objective: This study aims to describe the internal audit carried out and the impact on the quality of the financial statements of SD Muhammadiyah 3 Ikrom. Method: This study uses a qualitative research method using data collection techniques through observation, interviews and documentation. Results: The results of this study show that the implementation of regular internal audits can increase the transparency and accountability of financial statements, despite obstacles such as limited human resources and lack of understanding of the accounting field. Novelty: Financial Statements have a very crucial role in creating transparency and accountability as well as responsibility for fund management, one of which is in the world of Education, namely Elementary Schools. As a public sector agency, the School also implements internal audit as a form of accountability to the public, internal audit is one of the tools to assess the performance of the agency's financial management, the effectiveness of financial management, as well as identify system weaknesses and ensure compliance with regulations is carried out properly.